2015
DOI: 10.1016/j.phrs.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Connexin hemichannels influence genetically determined inflammatory and hyperproliferative skin diseases

Abstract: Connexin mutations underlie numerous human genetic diseases. Several connexin genes have been linked to skin diseases, and mechanistic studies have indicated that a gain of abnormal channel function may be responsible for pathology. The topical accessibility of the epidermal connexins, the existence of several mouse models of human skin disease, and the ongoing identification of pharmacological inhibitors targeting connexins provides an opportunity to test new therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 148 publications
0
15
0
Order By: Relevance
“…Interestingly, mutation of the A88 residue to serine, which does not cause KID syndrome, only has recessive and modest effects on CO 2 sensitivity. The main hypothesis for the effects of the dominant missense mutations of Cx26 causing syndromes is that there is a gain of functionthrough increased hemichannel activity (Levit et al 2014;Levit and White 2015;Lilly et al 2016). Our data now provide an alternative or additional potential hypothesisthat the loss of CO 2 -dependent modulation of hemichannel gating could contribute to pathology, at least for some mutations of Cx26.…”
Section: Implications For Etiology Of Kid Syndromementioning
confidence: 70%
“…Interestingly, mutation of the A88 residue to serine, which does not cause KID syndrome, only has recessive and modest effects on CO 2 sensitivity. The main hypothesis for the effects of the dominant missense mutations of Cx26 causing syndromes is that there is a gain of functionthrough increased hemichannel activity (Levit et al 2014;Levit and White 2015;Lilly et al 2016). Our data now provide an alternative or additional potential hypothesisthat the loss of CO 2 -dependent modulation of hemichannel gating could contribute to pathology, at least for some mutations of Cx26.…”
Section: Implications For Etiology Of Kid Syndromementioning
confidence: 70%
“…Recently, reported that HCs formed by expression of several Cx26 KID mutants in Xenopus laevis oocytes are inhibited by mefloquine (IC 50 w 16 mM). It needs to be investigated whether specific inhibitory compounds for Cx HC can be used to repress the inflammatory and septic features of KID mutations in the skin of mouse models and eventually in patients with KID (Levit and White, 2015).…”
Section: Comparison Of Kid Mouse Models and Patients With Kidmentioning
confidence: 99%
“…Dominant Cx26 mutations underlying syndromic deafness associated with severe often fatal skin disorders exemplified by keratitis-ichthyosis-deafness (KID) syndrome, Vohwinkel syndrome, and Bart-Pumphrey syndrome are less common. 25 syndromic mutations have been identified, most of which map to the N-terminus and to the region of the channel pore formed by the first transmembrane helix (TM1) and first extracellular loop (E1) [12, 13]. Mutations of Cx32 cause X-linked Charcot-Marie-Tooth (CMT-X) disease, a late onset peripheral neuropathy [14], which in some cases has central nervous system involvement [15, 16].…”
Section: Introductionmentioning
confidence: 99%